Helminth Coinfection Is Associated With Enhanced Plasma Levels of Matrix Metalloproteinases and Tissue Inhibitor of Metalloproteinases in Tuberculous Lymphadenitis - Kathamuthu, Gokul Raj; Moideen, Kadar; Thiruvengadam, Kannan; Sridhar, Rathinam; Baskaran, Dhanaraj; Babu, Subash (Frontiers in Cellular and Infection Microbiology, 2021)
Matrix metalloproteinases (MMPs) are crucial for tissue remodelling and repair and are expressed in diverse infections, whereas tissue-inhibitors of metalloproteinases (TIMPs) are endogenous inhibitors of MMPs. However, the interaction of MMPs and TIMPs in tuberculous lymphadenitis (TBL) an extra-pulmonary form of tuberculosis (EPTB) and helminth (Hel+) coinfection is not known. Therefore, this present study investigates the levels of circulating MMPs (1, 2, 3, 7, 8, 9, 12, 13) and TIMPs (1, 2, 3, 4) in TBL individuals with helminth (Strongyloides stercoralis [Ss], hereafter Hel+) coinfection and without helminth coinfection (hereafter, Hel-). In addition, we have also carried out the regression analysis and calculated the MMP/TIMP ratios between the two study groups. We describe that the circulating levels of MMPs (except MMP-8 and MMP-12) were elevated in TBL-Hel+ coinfected individuals compared to TBL-Hel- individuals. Similarly, the systemic levels of TIMPs (1, 2, 3, 4) were increased in TBL-Hel+ compared to TBL-Hel- groups indicating that it is feature of helminth coinfection per se. Finally, our multivariate analysis data also revealed the changes in MMPs and TIMPs were independent of age, sex and culture status between TBL-Hel+ and TBL-Hel- individuals. We show MMP-2 ratio with all TIMPs were significantly associated with TBL-helminth coinfection. Thus, our results describe that helminth infection has a profound effect on the pathogenesis of TBL and both MMPs and TIMPs could dampen the immunity against the TBL-Hel+ coinfected individuals.